Management Practice and Contributing Risk Factors for Chronic Complications Among Type 2 Diabetes Mellitus Adult Patients in Follow-Up at a Tertiary Care Teaching Hospital - Negash Z (Dove Medical Press, 2020)
Zenebe Negash, Malede Yismaw Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Zenebe NegashDepartment of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Zambia Street, PO Box 9086, Addis Ababa, EthiopiaTel +251 931726546Email zenebe.negash@aau.edu.etBackground: Diabetes Mellitus is a complex, chronic disease that requires a coordinated management practice beyond blood glucose control. The disease causes chronic complications that affect the quality of the life of patients, place major pressure on the health-care system and cause a rise in diabetes-related mortality.Objective: To determine the prevalence of chronic diabetes mellitus complications, related risk factors, and management practice among adult type 2 diabetes mellitus outpatients at Tikur Anbessa Specialized Hospital (TASH).Methods: A cross-sectional study design was carried out from July to September 2018. The pre-tested data abstraction format was used to gather demographic and clinical information. We also used a balance of weight measurement, upright placed meter for height measurement, waist circumference measurement meter and BP equipment. Statistical analysis was accomplished using Statistical Package for the Social Sciences (SPSS) 25® software. The significance level for statistics was set at p< 0.05.Results: In this study, 320 patients were involved. Of these, about 57% were female and had a mean age of 58 ± 11.2 years. About 85% of the study participants had comorbidity and 42.5% had complications. Hypertension and neuropathy were the most common comorbidity and complication, respectively. The usage of vascular preventive medication among study participants was 74.7% and 55.3% for statins and ASAs, respectively. Participants in the study who had disease duration of 5– 10 years (AOR=3.50, 95% CI: 1.19– 10.28) and fifteen and above (AOR= 3.59, 95% CI: 1.36– 9.49) were at higher risk of diabetes complication as compared to less than five years.Conclusion: The prevalence of chronic complications was high among adult T2DM outpatients. The duration of disease and the number of medications used were the factors associated with chronic complications. The use of vascular preventive medications was low among study participants.Keywords: type 2 DM, diabetes complication, risk factors, vascular-preventive medications